Does personality dysfunction add incremental utility over general psychopathology when modeling previous suicide attempts in adolescent patients? - Hertel, Christian; Cavelti, Marialuisa; Lerch, Stefan; Mürner-Lavanchy, Ines M.; Reichl, Corinna; Koenig, Julian; Kaess, Michael (Journal of affective disorders, 2024)
Background - Identifying patients at risk for a suicide attempt (SA) is critical in adolescents with mental disorders. The current study aimed to 1) examine whether personality dysfunction (PD) is associated with previous SA, 2) explore the incremental utility of PD over psychiatric disorders in modeling previous SA. - Methods - The sample comprised of n = 498 adolescent patients (mean age = 15.41 years, 79.12 % females, inpatient 48.8 %, outpatient 51.2 %). SA in the past year, PD according to the alternative DSM-5 model for personality disorders, and psychiatric diagnoses were assessed using semi-structured interviews. Logistic regression and principal component analysis examining the associations and specific patterns of PD and SA in the past year were conducted. Hierarchical (stepwise) logistic regression was applied to investigate the incremental utility of PD over that of psychiatric diagnoses to identify individuals with SA in the past year. - Results - Including all facets of PD revealed a significant model with SA in the past year as outcome (χ2(12) = 106.65, McFaddens Pseudo-R2 = 0.17, p < 0.01). Adding PD to the model explained a significant amount of variance in past SA over that of psychiatric diagnoses (Pseudo-R2 = 0.18, Wald χ2 = 43.05, p < 0.01). - Limitations - As we only studied past SA and due to the cross-sectional design, no conclusion regarding the prediction of future SA can be drawn. - Discussion - PD should routinely be assessed in adolescent patients since individuals with PD are more likely to have attempted suicide even when controlling for comorbid psychiatric disorders. PD may represent an important target for intervention in those with suicidal thoughts and behaviors.
Online verfügbar 17 June 2024, Version des Artikels 22 June 2024
Gesehen am 13.12.2024